The Influence of PhET-Assisted STEM Learning Model on Understanding the Concept of Motion Transformation in Physics - Pribadi, Pandu; Jamali, Arif; Nurahman, Arip; Anwar, Khairil; Fiqry, Rizalul (Bincang Sains dan Teknologi, 2025)
This study aims to analyze the effect of the PhET-assisted STEM learning model on the understanding of motion transformation concepts among students at Muhammadiyah Langkaplancar Junior High School. The concept of motion transformation includes translation, rotation, and acceleration, which are abstract and often difficult for students to understand. To overcome this, PhET is used as an interactive simulation medium that allows students to manipulate variables directly and observe their effects in real time. The research method uses an experimental design with pre-tests and post-tests. The research sample consisted of 20 ninth-grade students selected at random. The research instruments were concept comprehension tests, observations, and student learning experience questionnaires. The results showed an increase in the average comprehension score of 20 points in the experimental group, while the control group only increased by 4 points. Although the ANOVA test did not show a statistically significant difference between the two groups (p-value 0.95), PhET-assisted learning was proven to increase interactivity and the quality of physics learning. In conclusion, the application of the PhET-assisted STEM learning model can be an alternative innovative strategy to strengthen the understanding of complex physics concepts at the junior high school level, while encouraging student motivation and engagement in the learning process.